Pemanfaatan Humas Siber pada Akun Instagram Band Musik Dangdut Guyon Waton - Ismail Taufik Rusfien; Maurent Nisa Adesty (Syntax Corporation Indonesia, 2024)
This research aims to find out how the band Guyon Waton's cyber public relations is used on Instagram. This research uses a qualitative method with a descriptive approach which uses the concept of Puspitasari and Purwani theory which is generally carried out through the use of Cyber Public Relations namely, Constant Internet Communication, Fast Internet Response, Internet Global Market, Interactive, Two-way Communication, and Economical . The results of this research show that the use of cyber public relations on Instagram by the Guyon Waton band is quite good in several ways based on analysis, namely, constant internet communication, fast internet response, global internet market, interactive, two-way communication, and economical. Guyon Waton has a characteristic of uploading funny content and follower content to keep his followers connected and active. The conclusion is that Guyon Waton uses Instagram as a medium for publicizing band activities. In its use, Guyon Waton carries out communication in a unique way, namely replying to DM messages which are then uploaded to Instagram stories. Apart from that, another unique way is to upload funny memes and some viral content to bring to life the meaning of Guyon Waton itself, namely outrageous jokes. In this unique way, Guyon Waton has so many fans that it has earned the title of band with the most followers in Indonesia at 1.5 million followers.